Description of a new species of Laelaspis Berlese (Acari: Mesostigmata: Laelapidae) from Brazil, with a key to the species of the Western Hemisphere - Duarte, Adriane Da Fonseca; Rueda-Ramírez, Diana; Da Cunha, Uemerson Silva; Moreira, Grazielle Furtado (Zootaxa, 2022)
Laelaspis loeckii Duarte & Moreira sp. nov. is described based on the morphology of adult females and males collected from soil in a survey carried out in southern Brazil, in the temperate Pampa biome. This is the first species of this genus described from this country. A key to the species that have so far been reported from the Western Hemisphere is provided.